Ensino de química e justiça ambiental: um estudo qualitativa em três escolas no entorno da Refinaria de Duque de Caxias (REDUC) - Souza, Marcia Olivieri de (2013)
This dissertation describes how the refining of petroleum and its environmental impacts are addressed in the curriculum of science education in three schools located in the vicinity of the Refinery Duque de Caxias (REDUC), at Baixada Fluminense. The study was designed as an exploratory research. Research participants were ninth grade students and science teachers. Data was collected through observations, interviews, questionnaires and three focus groups from August 2011 to March 2013. The theoretical framework drew on the literature on environmental justice, critical environmental education, science-technology-society-environment and the chemistry of petroleum. The notion of environmental justice includes the right to a healthy, safe and productive environment for everyone. In this perspective the environment is considered in its ecological, social, physical, economic, political and aesthetic dimensions. Results indicated that the curriculum of science education at the three schools was limited to the teaching of basic contents prescribed in official programs and textbooks. Aspects related to the refining of petroleum and its impacts were discussed informally, as a personal initiative of some teachers. Research participants also stated that the Refinery Duque de Caxias was not developing educational projects in partnership with schools during the period of the study. Results revealed that few students knew how brute petroleum was being refined in their neighborhood, but were able to list the impacts of the Refinery in their health. The study suggested that schools located in the vicinity of major oil industries must have teaching resources and curriculum guidelines specially designed to promote environmental justice and citizenship. In the light of such results, the final product of this professional master course is a blog with contents related to the chemistry of petroleum in the perspective of a critical environmental education.